Anti-granulocyte opsonic activity in sera from patients with systemic lupus erythematosus. - Hadley, A; Byron, M; Chapel, H; Bunch, C; Holburn, A (1987)
Neutropenia is common in patients with systemic lupus erythematosus (SLE) but mechanisms of cell depletion remain obscure. To investigate the possible autoimmune aetiology of neutropenia in SLE, sera from 31 patients with this disorder were tested for anti-granulocyte activity. Granulocyte-binding immunoglobulins were detected by indirect immunofluorescence, and the ability of patient sera to opsonize granulocytes was determined by measuring the chemiluminescent response of human monocytes to granulocytes sensitized by test sera. Sera from 22 of the 31 patients bound IgG to granulocyte cell membranes and/or to nuclei, but only membrane-binding antibodies opsonized the cells for recognition by monocytes. There was no correlation between neutrophil count and the level of granulocyte-binding IgG as measured by indirect immunofluorescence. In contrast, opsonic activity and neutrophil count were inversely correlated (r = 0.5; P less than 0.05). However, opsonic activity was present in sera from most non-neutropenic patients. In patients with SLE, impaired reticuloendothelial system function may allow sensitized granulocytes to remain in the circulation.